Analysis of an unselected patient cohort with advanced colorectal carcinoma from a maximum care center - Zhang, Xin-Wen; Mohr, Jutta; Halama, Niels; Koschny, Ronald (Anticancer research, 2023)
Background/Aim: Systemic treatment for metastatic colorectal cancer (CRC) includes chemotherapy in combination with a targeted antibody. Novel targeted therapies and immunotherapies are introduced for specific molecular subgroups. Prognostic relevant determinants are still under investigation. Patients and Methods: Systemic therapies of an unselected patient cohort with metastatic CRC were retrospectively analyzed. Treatment outcome was evaluated according to time-to-next-treatment (TTNT) and frequency of conversion surgery and compared between subgroups stratified by primary tumor side, molecular profile, sex and age, and metastases sites. Results: More than 50% of patients with locally advanced or metastatic CRC underwent secondary resection after first-line systemic therapy. Rectum carcinoma had the best prognosis under anti-EGFR-antibody treatment. Female patients had a worse prognosis than male patients in late disease stage. Young patients demonstrated poor response to systemic therapy, but a high rate of conversion surgeries. Conversely, elderly patients benefited from systemic therapy but underwent surgery less frequently. Liver and lung metastases had a worse prognosis than other metastases sites, whereas lung metastases were more likely to be resected than liver metastases in early disease stage. Conclusion: Patient age, sex, primary tumor localization, and metastatic sites are prognostic factors that could guide future treatment decisions for the therapy of metastatic CRC.